Risk Analysis on the Cassava Value Chain in Central Lampung Regency - Ani Suryani; Masyhuri Masyhuri; Lestari Rahayu Waluyati; Arini Wahyu Utami (AGRARIS: Journal of Agribusiness and Rural Development Research, 2023)
The Central Lampung Regency is the center of cassava production in Lampung Province, the Indonesia’s largest cassava-producing province. Cassava has much promise; however, various risks arise throughout the value chain. Risks in the agricultural sector, including cassava farming, are unavoidable and severely impact stakeholders and consumers. This study aimed to identify the risks and the most effective mitigation measures for the cassava value chain. This research was conducted using the House of Risk (HOR) method, divided into two phases: HOR 1 and HOR 2. It involved 286 samples encompassing 263 farmers, six traders, three tapioca industries, eight non-tapioca industries, and six financial institutions. The risks were determined through the Supply Chain Operational Reference (SCOR) model. The results unveiled several priority risks in the cassava value chain, consisting of unpredictable weather changes, scarcity of fertilizers, the absence of farming standards, limited capital, delivery technical problems, price fluctuations, negligence of the workforce, default credit, and lack of customer or farmer knowledge leading to confusion. Furthermore, the risk mitigation actions covered preventing the risks of cassava farming; applying appropriate technology; utilizing production, marketing, and financing system assistance; preventing the risks of cassava trading business; implementing a structured market system; developing access to financing, institutions, and markets; developing marketing infrastructure; developing adaptive farming; monitoring during the credit period; socializing risk management to employees; and providing institutional, financing, and production assistance.